Save the last dance (Paramount Pictures, 2001)
When her mother suddenly dies, Sara must abandon her plans to become a ballerina and join her estranged father on Chicago's gritty South side. She feels out of place until she is befriended by a black classmate and her brother, Derek. Sara and Derek's shared love for dance leads to romance-- and opposition from their families and friends.